Panton-Valentine Leukocidin in the Pathogenesis of Community-associated Methicillin-resistant Staphylococcus aureus Infection - Wen-Tsung Lo; Chih-Chien Wang (Elsevier, 2011)
Methicillin-resistant Staphylococcus aureus (MRSA) is an important human pathogen that causes serious infectious diseases and was endemic in hospitals by the late 1960s. Beginning with its first report in the late 1990s, the rapid emergence of community-associated MRSA (CA-MRSA) worldwide responsible for a wide spectrum of diseases ranging from minor skin infections to fatal necrotizing pneumonia has been found in previously healthy individuals without established risk factors for MRSA acquisition. Recently, various virulence determinants unique to CA-MRSA have been uncovered, which explain how the pathogen spreads easily and causes severe CA-MRSA infections among humans. However, the role of Panton-Valentine leukocidin (PVL) in the pathogenesis of CA-MRSA infection is currently a matter of much debate because of conflicting data from epidemiologic studies of CA-MRSA infections and various murine disease models. Identifying specialized pathogenic traits of CA-MRSA and the concerted regulation of these factors remains a challenge that will foster development of vaccines and therapies designed to control CA-MRSA infections. This review focuses on the current status of molecular epidemiology associated with CA-MRSA in Taiwan and progresses toward understanding the enhanced virulence properties of CA-MRSA, with an emphasis on the role of Panton-Valentine leukocidin.